Implications Quality Report Finance and Systems Internal Control of Local Government Performance The Role of Accountability as Mediation (Study at Cilegon City Government Banten) - Hadiatul, Umi; Bastian, Elvin; Ramdhani, Dadan (AFEBI Accounting Review, 2023)
Abstract Study This test how much influence quality report financial and internal control systems in the public sector. The government performance area is the main factor tested in the study This as well as using the accountability factor as a mediator. Sample from study This is an organization device government area (OPD). city Cilegon. The method study uses an approach quantitative with SEM method and smart PLS software. Findings study This concludes that quality report finance is influential and significant the internal control system is also influential and significant to the performance of government area. Whereas accountability is mediation capable mediate the connection between quality reports to performance. However, no capability mediates the relationship between quality reports to performance. Implications study this hope can become input for policy government area specifically to the role from factor quality report financial and internal control system as well accountability to policy sector accountancy public sector management. Key Words: quality report finance, internal control system, government performance, accountability, and accounting management public sector.